2017
DOI: 10.18632/oncotarget.19699
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq based gene expression analysis of ovarian granulosa cells exposed to zearalenone in vitro: significance to steroidogenesis

Abstract: Zearalenone (ZEA) is a natural contaminant of various food and feed products representing a significant problem worldwide. Since the occurrence of ZEA in grains and feeds is frequent, the present study was carried out to evaluate the possible effects of ZEA on steroid production and gene expression of porcine granulosa cells, using RNA-seq analysis. Porcine granulosa cells were administered 10 μM and 30 μM ZEA during 72 h of culture in vitro. Following ZEA treatment the gene expression profile of control and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
(53 reference statements)
2
14
1
Order By: Relevance
“…However, the authors stated that mares fed with the naturally contaminated oats had a high incidence of follicular hematomas, which did not occur in the control ( Cortinovis et al, 2013 ). Similar to the findings in estrous pig ( Zhang et al, 2017b ), ZEA and its derivatives induced in vitro apoptosis of the granulosa cells (GCs), which were collected from estrous mares’ ovaries ( Minervini et al, 2006 ). Hence, the authors suggested that ZEA could induce follicular atresia in domestic animals.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, the authors stated that mares fed with the naturally contaminated oats had a high incidence of follicular hematomas, which did not occur in the control ( Cortinovis et al, 2013 ). Similar to the findings in estrous pig ( Zhang et al, 2017b ), ZEA and its derivatives induced in vitro apoptosis of the granulosa cells (GCs), which were collected from estrous mares’ ovaries ( Minervini et al, 2006 ). Hence, the authors suggested that ZEA could induce follicular atresia in domestic animals.…”
Section: Introductionsupporting
confidence: 70%
“…Numerous studies have proven ZEA’s cytotoxic effect on the reproductive ( Kiang et al, 1978 ; Mehmood et al, 2000 ; Nikov et al, 2000 ), immune ( Abbes et al, 2006a , b ; Luongo et al, 2006 ), and endocrine ( Mueller et al, 2004 ) systems, as well as on heredity ( Kouadio et al, 2005 ). ZEA indirectly affects mammalian fertility by impairing the formation of primordial follicle ( Zhang et al, 2017a ), thereby causing changes in gene expression; it also induces DNA damage in ovarian GCs ( Zhang et al, 2017b ). Not much information is available on ZEA-induced alteration in dGC proliferation and development and impairment of mammalian fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis of ovarian granulosa cells directly or indirectly results in the reduction of germ cells, which plays a crucial role in the determination of the number of follicles destined to ovulate in each reproductive cycle (Gebauer, Peter, Onesime, & Dhanasekaran, ). However, there are many toxins of fodder that were found to have a negative effect on ovarian granulosa cells such as 2,5‐hexanedione (2,5‐HD), T‐2 toxin and zearalenone (ZEN) (Wu, Tu, Yuan, Yuan, & Wen, ; Zhang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…E. asinus , that were fed naturally ZEA-contaminated oats, had a high incidence of follicular hematomas, which did not occur during control cycles (Cortinovis et al, 2013). ZEA and its derivatives induced the apoptosis of GCs collected from the ovaries of cycling mares in vitro (Minervini et al, 2006) and from cycling pigs (Zhang et al, 2017b). Considering the contemporaneous presence of both processes, authors suggested that ZEA could induce follicular atresia in domestic animals.…”
Section: Introductionmentioning
confidence: 99%